Neonatal hyperoxia induces gut dysbiosis and behavioral changes in adolescent mice. Issue 3 (3rd March 2021) - Lo, Yu-Chun; Chen, Kai-Yun; Chou, Hsiu-Chu; Lin, I-Hsuan; Chen, Chung-Ming
Abstract : Background: Supplemental oxygen is often required to treat preterm infants with respiratory disorders. Experimental studies have demonstrated that hyperoxia results in the disruption of intestinal and neuronal plasticity and myelination of the brain. The association between the neonatal hyperoxia and changes of phenotypes in gut microbiota and in behaviors is not clear to date. Methods: We designed an animal experiment that C57BL/6 mice pups were reared in either room air (RA) or hyperoxia (85% O2 ) from postnatal days 1 to 7. From postnatal days 8 to 42, the mice were reared in RA. Intestinal microbiota was sampled from the lower gastrointestinal tract on postnatal days 7 and 42, and behavioral tests were performed and brain tissues were collected on postnatal day 42. Results: Neonatal hyperoxia decreased intestinal tight junction protein expression and altered intestinal bacterial composition and diversity on postnatal day 7. Among the concrete discriminative features, Proteobacteria and Epsilonbacteraeota were significantly elevated in hyperoxia-reared mice on postnatal days 7 and 42, respectively. Hyperoxia-reared mice exhibited significantly reduced sociability and interest in social novelty and impaired motor coordination compared with RA-reared mice on postnatal day 42. Hyperoxia-reared mice also exhibited significantly reduced myelination and a significantly higher number of apoptotic cells in the brain compared with RA-reared mice on postnatal day 42. Conclusion: Neonatal hyperoxia during the first week of life altered gut microbiota and reduced brain myelination that might associate with the deficits of social interaction and motor coordination in adolescent mice.